Barriers in services trade: The state of negotiations and prospects - Siegfried Schultz (Intereconomics, 1993)
Trade in services constitutes one of the still unresolved problems in the Uruguay Round. What progress has been made so far in this field? Which are the remaining points at issue? What are the prospects for agreement on a comprehensive solution?
Keywords: 330; Uruguay Round